Efektivitas latihan renang resistance band terhadap kekuatan otot pada perenang tuna daksa di nomor 50 meter gaya bebas - Hartono, Fajar Vidya; Sukur, Abdul; Miftakhudin, Heru; Marhadi, Marhadi (Universitas Nusantara PGRI Kediri, 2024)
Resistance band training can increase muscle strength in swimmers with physical disabilities, especially because muscle strength problems often hinder achieving optimal performance. This study aimed to determine the effect of resistance band training on the muscle strength of swimmers with physical disabilities number 50 meters freestyle. This research method uses a one-group pretest-posttest design with an experimental approach. This study used a one-group pretest-posttest pre-experimental design research design. This research instrument used a total sampling recruitment technique involving 28 Jakarta Para Swim athletes. PretestPretest and post-test tools, including a 50-meter freestyle swimming course, were used in this study. Using IBM SPSS Statistics version 27, data analysis methods included a t-test at a significant level of 0.05, normality and homogeneity tests, and prerequisite tests. The results of this study state that the average speed of 28 athletes is 42.21 freestyle meters before the test and 38.77 freestyle meters after the test there is an increase in the average speed of 50 meters freestyle by 10%, or 3.44 seconds in resistance band training for swimmers with disabilities number 50 meters freestyle with an increase of 10%, namely 3.44 seconds. These results provide a basis for disability sports coaches and practitioners to integrate resistance band training as part of a training program to improve swimming performance for athletes with physical disabilities.